Superior haplotypes of genes associated with higher grain yield under reproductive stage drought stress in rice - Singh, Preeti; Pahi, Bandana; Sundaram, Krishna T.; Gnanapragasam, Niranjani; Habde, Sonali Vijay; Kumar, Nandigam Vinay; Patil, Namrata Devidas; Paul, Pronob J.; Kumar, Ravi Shekhar; Singh, Suresh Prasad; Kalia, Sanjay; Kumar, Arvind; et al. (Oxford University Press, 2025)
Understanding the genetic basis of reproductive stage drought tolerance (RSDT) requires bridging genomic variations with phenotype. This study employed a genome-wide association study (GWAS) using 450 rice accessions for grain yield under reproductive stage drought stress across three locations and two seasons. The results revealed 67 marker–trait associations (MTAs) that corresponded to 23 candidate genes. Superior haplotypes were identified for 10 RSDT-related genes, namely SAP-H22, WRKY109-H6, OsIRO2-H3, OsSOBIR1-H68, OsPGL31-H8, OsDAHPS1-H2, ZCD-H13, OsMC2-H8, Ospdr9-H16, and SDR-H2. These genes are involved in stress-related processes such as transcription regulation, cell wall structure modification, leaf rolling, programmed cell death, redox stress, and secondary metabolite accumulation. Notably, introgressing superior haplotypes from the OsIRO2-H3 gene into an elite rice cultivar led to a yield advantage of 25.0–27.3% over recurrent parents. These findings highlight the potential of these genes as valuable resources for breeding high-yielding, drought-tolerant rice varieties.